Benefits of respiratory-gated 18F-FDG PET acquisition in lung disease. Issue 1 (January 2018) - Bailly, Pascal; Bouzerar, Roger; Shields, Trevor; Meyer, Marc-Etienne; Daouk, Joël
Abstract : Background: Fluorine-18-fluorodeoxyglucose ( 18 F-FDG) PET/computed tomography (CT) is a reliable imaging modality for the diagnosis of malignant lung nodules and to assess the latter's prognosis. However, physiological respiratory motion deteriorates PET images and thus decreases the technique's diagnostic and prognostic values. This issue can be overcome by applying respiratory gating to the 18 F-FDG PET/CT acquisitions. Purpose: The aim of this study was to evaluate the ability of respiratory-gated 18 F-FDG PET/CT to diagnose malignant lung nodules and to predict recurrence and patient survival. Patients and methods: A total of 103 prospectively enrolled patients with solid lung nodules underwent both ungated and gated 18 F-FDG PET/CT acquisitions. The maximum standardized uptake value (SUVmax ) was used to differentiate benign from malignant nodules. Patients have been followed up for at least 36 months to confirm imaging results and assess survival. Results: Gated 18 F-FDG PET/CT was significantly more sensitive than ungated PET/CT for the diagnosis of malignant lung nodules located in the lower lobes (92 vs. 58%; P <0.001) and in patients aged older than 60 years (73 vs. 48%; P <0.001). The same gain was observed for stage I cancers with tumors from 10 to 20 mm. When considering patients aged older than 60 years, those with a low SUVmax on gated PET images had a significantly higher 3-year disease-free survival rate than those with a high SUVmax (76 vs. 47%; P =0.03). Conclusion: 18 F-FDG PET/CT is advisable for the assessment of lung nodules in patients aged older than 60 years and/or in the lower lobes.